Determination of Optimum Mechanical Drilling Parameters for an Iraqi Field with Regression Model - Abdul Hussien, Hassan; Abdullateef, Dahlia (Iraqi Journal of Science, 2023)
An optimization analysis of drilling process constitutes a powerful tool for operating under desired pressure levels and simultaneously maximizing the penetration rate, which reduces costs and time thus increases the profit.In this study, a composite drilling model (Young-Bourgyen model) of eight functions was used to determine the optimum drilling mechanical parameters (Weight on bit and rotary speed) for an Iraqi oil field. These functions model the effect of most drilling parameters such as formation strength, mud density, formation compaction, weight on bit, rotary speed, tooth dullness, and bit hydraulic on drilling rate. Data are extracted from bit record and drilling report of well BUZ-20 for calculation of eight exponents of the model with regression analysis method. For each formation within the geologic section of drilled well, the drillability constant was calculated .The rate of penetration for the field had been predicted based on constants for every data against depth, and noticeable differences between them were observed . Also, an optimized weight on bit and rotary speed had been calculated for several data point.